Activation Control System in Motorized Vehicles Using the Global Positioning System (GPS) - Aris Budiyarto; Abdur Rohman Harits Martawireja; Mohammad Harry Khomas Saputra; Gun Gun Maulana (CESS (Journal of Computer Engineering, System and Science), 2023)
In Indonesia, the theft rate is still quite high. According to Bappeda data, cases of theft still tend to be high. In 2019, there were 362,000 cases of theft. CCTV use is still ineffective because at the time of the theft of goods, we only know the goods taken and the perpetrators. In order to catch the perpetrators and return the goods, it is necessary to process them first and find the location of the perpetrators themselves. Therefore, we propose an idea entitled "Activation Control System in Motorized Vehicles Using GPS". Where this tool will detect the position of a vehicle so that this vehicle remains in a restricted area. When this vehicle leaves the restricted area, the GPS system will send a signal explaining that the vehicle is leaving the area. So, if there is a theft, when the vehicle has moved away from about 50 meters from the area that has been locked, a notification will appear which will be displayed on the web application. The research stages that we will work on are first identifying the equipment and systems that will be used and conducting a study of the technology literature that will be developed, then identifying the theoretical and empirical system design and knowing the basic elements. Then master and understand the characterization of components and analyze the main functions so that they can work properly. Then do modelling and simulation and ensure that the components to be developed can work properly. And the final stage is to ensure that the system equipment is valid and reliable. Based on the results of the study, it shows that the system is active when the actual position away from the locked position/area as far as 100 meters has successfully functioned. Where the information changes to "Out of reach" from the previous "Within Reach" and there are notifications in the form of sound and vibration to increase security from theft.